Answer:
I dont know about that??????
2 because the equation can be reduced to: 8.0 x 10^4.
Answer:
( z - 5 ) ( z - 5 )
Step-by-step explanation:
z² − 10z + 25
= z² − 5z - 5z + 25
= z ( z - 5 ) - 5 ( z - 5 )
= ( z - 5 ) ( z - 5 )
Answer:
293 seconds
Step-by-step explanation:
60*4=240
240+53=293
<span>Given:
x g(x)
−3 17
−1 −3
0 −4
2 13
The true statement for the given function is:
</span><span>The function is decreasing from x = −3 to x = −1.
</span><span>
As you can see, when x = -3 the corresponding value of the function is 17 but when x = -1 the corresponding value is -3. There is a decrease of 20. </span>→<span> 17 - 20 = -3
</span>